Autoinflammatory/Autoimmunity Syndrome Induced By Adjuvants (ASIA) Due to Silicone Incompatibility Syndrome - Genessis Maldonado; Roberto Guerrero; Maria Intriago; Carlos Rios (Case Reports in Rheumatology)
The adjuvant-induced autoimmune syndrome (ASIA) is associated with a dysregulation of the innate and adaptive immune system after exposure to chemical compounds, including liquid paraffin, silicone gel, acrylamides, and hyaluronic acid. Due the increase of the use of these compounds in cosmetic procedures, the prevalence of this syndrome is increasing. We present the first report in Ecuador associated to ASIA after an elective silicone breast prosthesis procedure, manifested as polyarthralgia, positive antinuclear antibody, anticentromere antibody, and a moderate positive Sclero-70.